Critical approaches to security in Central Asia - Lemon, Edward (Central Asian studies series, 2019)
Central Asia remains on the periphery, both spatially and in people's imaginations. When the region does attract international attention, it is often related to security issues, including terrorism, ethnic conflict and drug trafficking. This book brings together leading specialists from a range of disciplines including geography, anthropology, sociology and political science to discuss how citizens and governments within Central Asia think about and practise security. The authors explore how governments use fears of instability to bolster their rule, and how securitized populations cope with (and resist) being labelled threats through strategies that are rarely associated with security, including marriage and changing their appearance